Arbovirus Surveillance near the Mexico–U.S. Border: Isolation and Sequence Analysis of Chikungunya Virus from Patients with Dengue-like Symptoms in Reynosa, Tamaulipas - Garza Hernandez, Javier Alfonso (2018)
A total of 1,090 residents of the city of Reynosa, Tamaulipas, on the Mexico–U.S. border presented at hospitals and clinics of the Secretariat of Health, Mexico, in 2015 with symptoms characteristic of dengue. Dengue virus (DENV) antigen was detected by enzyme-linked immunosorbent assay in acute sera from 134 (12.3%) patients. Sera from select patients (N = 34) were also tested for chikungunya virus (CHIKV) RNA by quantitative reverse transcription–polymerase chain reaction. Thirteen (38.2%) patients, including five DENV antigen-positive patients, were positive. Sera from three CHIKV RNA-positive patients were further assayed by virus isolation in cell culture and CHIKV was recovered on each occasion. The genome of one isolate and structural genes of the other two isolates were sequenced. In conclusion, we present evidence of CHIKV and DENV coinfections in patients who live near the Mexico–U.S. border and provide the first genome sequence of a CHIKV isolate from northern Mexico.